DESCRIPTIVE STUDY OF WOMEN'S LABOR FORCE PARTICIPATION RATE IN THE BOJONEGORO RESIDENCY IN 2016-2020 - Ali Zainal Abidin (MESP–FEB UNS, 2022)
The phenomenon of the entry of women into the world of work indicates the development of the function and role of women in the family and society. Not only as mothers and wives, now women are starting to take on the duties of a worker. Women's participation in the labor market can be seen through the labor force participation rate indicator or LFPR. LFPR can show the percentage of the female workforce among several residents of an area in a certain period. This study aims to explain women's LFPR, especially those in the former Bojonegoro Residency area in the 2016-2020 period. The method used is a quantitative descriptive method. The data used is secondary data from BPS and related publications in several editions. The results showed that the LFPR of women in the former Bojonegoro Residency area increased from year to year, from 2016-2020. In 2016, the LFPR of women in the former Bojonegoro Residency area was 33.54% and increased to 38.6% in 2020. This increase proves an increase in women's participation in the job market, especially in the former Bojonegoro Residency area.